1992
DOI: 10.1007/bf03008373
|View full text |Cite
|
Sign up to set email alerts
|

Measuring recovery from general anaesthesia using critical flicker frequency: A comparison of two methods

Abstract: Measuring

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 9 publications
0
7
0
1
Order By: Relevance
“…The LEDs were activated by a specially designed motherboard controlled through specific software with a notebook. For each individual tested, two methods were used, the continuous flicker method (CFM) (3) and the forced‐choice method (FCM) (6). The subjects were asked to focus on the four LEDs during all the recording procedures.…”
Section: Methodsmentioning
confidence: 99%
“…The LEDs were activated by a specially designed motherboard controlled through specific software with a notebook. For each individual tested, two methods were used, the continuous flicker method (CFM) (3) and the forced‐choice method (FCM) (6). The subjects were asked to focus on the four LEDs during all the recording procedures.…”
Section: Methodsmentioning
confidence: 99%
“…The CFF analysis is a method widely used to evaluate the effects of various drugs on vigilance and continuous performance. 6,7,8 In a review presented by Smith and Misiak, 8 the results of 33 studies dealing with the influences of psychotropic drugs on the CFF are summarized. Additionally, this method has also been used to measure recovery after general anesthesia.…”
Section: Commentsmentioning
confidence: 99%
“…This method has already been proven to be useful to assess the effects of drugs on vigilance and continuous performance. 6,7,8 However, to our knowledge the evaluation of the CFF has not yet been applied to headache patients to differentiate between those with drug abuse and those without drug abuse.…”
mentioning
confidence: 99%
“…We thus also investigated how jumps could hamper cortical arousal using Critical Flicker Fusion Frequency (CFFF). The CFFF is non invasive and reliable in measuring cortical arousal (Hou et al 2007;Rota-Bartelink 1999) and has been demonstrated a good marker of cortical changes due to physical workload (Luczak and Sobolewski 2005;Luczak et al 1995;Davranche and Pichon 2005), drug administration (Hunter et al 1994;Hindmarch 1982), alcohol intoxication (Leigh 1982;Liu and Ho 2010;Schillaci and Fazio 1967), anaesthesia (Salib et al 1992;Sharma et al 2011;Wernberg et al 1980), encephalopathy (Ali et al 1994;Chang 1 3 et al 2007;Kircheis et al 2002;Lauridsen et al 2011) as well as hyperoxia (Balestra et al 2012;Hemelryck et al 2013). CFFF variations happen in parallel to EEG changes and are thus better than merely relying on subjective reports for neuropsychological defects (Seki and Hugon 1976).…”
Section: Introductionmentioning
confidence: 99%